Konsep Industrialisasi pada Perkembangan Teknologi - Khosnol Khotimah; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Technology is a set of principles or rational methods related to the creation of an object. At this time technology is increasingly sophisticated given that the times have developed rapidly. Many of these technological factors have affected the community and the surrounding environment with the passage of time and other things that can help or improve the community's economy. This technology is often used by people to achieve practical goals. The beginning of this technology is only a form such as equipment or machinery because technology is very rapidly developing until now and society is also very following technology.